2012
DOI: 10.1590/s1519-99402012000200001
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de propriedades leiteiras de Santa Catarina em relação à Instrução Normativa 51

Abstract: Santa Catarina é o quinto maior produtor de leite do país, sendo essa atividade uma importante fonte de renda para os produtores. Para a continuidade dessa realidade, torna-se importante que atendam às normas de qualidade do leite estabelecidas pela Instrução Normativa 51/2002 (IN 51). Com o objetivo de identificar o perfil de propriedades leiteiras e verificar a percepção dos produtores sobre as exigências de qualidade do leite estabelecidas pela IN 51, realizou-se uma pesquisa diagnóstica por meio da aplicaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
4
0
6
Order By: Relevance
“…Therefore, the use of equipment that minimizes the human workforce has been advocated by Hansen (2015). Wink and Thaler Neto (2012) reported that when there is a satisfactory average in milk production, producers can invest in the improvement of milking equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of equipment that minimizes the human workforce has been advocated by Hansen (2015). Wink and Thaler Neto (2012) reported that when there is a satisfactory average in milk production, producers can invest in the improvement of milking equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The average volume of milk commercialized (Table 1) shows the profile of dairy farms in the South of Brazil, with the extract formed by the first two quintiles (40% of the samples) selling up to 4,314 liters/month (Table 2), corresponding to approximately 140 liters of milk per day. Dairy farms in this region are mainly composed of small rural settlements, as demonstrated by works in Santa Catarina (WINCK;THALER NETO, 2012;WERNCKE et al, 2016), in Rio Grande do Sul (GABBI et al, 2013) and Paraná (LANGE et al, 2016). The ESD levels ( Figure 1A), as well as their main constituents (lactose and protein) ( Figure 1B) presented intense variation throughout the year, with lower levels of DDE in summer and fall, with high percentages of non-compliance in some months in these seasons ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…A relatively high DDE content was observed during the first month of lactation, falling in the second month and then increasing in late lactation, as a result of the variation in the protein content (HARRIS JÚNIOR;BACHMAN, 2003). In the South of Brazil, small dairy farms are predominate (WINCK;THALER NETO, 2012;GABBI et al, 2013;LANGE et al, 2016;WERNCKE et al, 2016) and the greatest differentiation between small dairy farms is related to how the cows are fed. (GABBI et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à idade dos produtores de leite, 28,5% dos produtores entrevistados possuem até 25 anos, 28,5% mais que 25 e até 35 anos e 43% possuem idade superior de 35 anos. Winck & Thaler Neto (2012) Outro fato considerável nas PL's foi o destino do leite produzido, onde a maioria das PL's (57,1%) destina-se o leite para queijarias e comércio informal (leite cru "in natura"), 14,2% para o consumo familiar e 28,7% para um laticínio do município. Do leite produzido nas PL's apenas 20,0% é refrigerado e 80,0% do leite produzido não é beneficiado com a refrigeração proposta por Brasil (2011).…”
Section: Caracterização Dos Produtores E Das Pl's a B C D E E Avalunclassified
“…Em 42,8% destas PL's existe o acompanhamento de um responsável técnico e 57,2% não constam da presença deste profissional. Winck & Thaler Neto (2012) encontraram que 64,5% dos produtores declararam que recebiam algum tipo de assistência técnica. Ainda sim, estes resultados foram próximos dos encontrados por Neves et al (2011) ao caracterizar os produtores e os sistemas de produção de leite no perímetro irrigado de Petrolina/PE e por Marcondes (2005) Observou-se que a higiene na ordenha é de suma importância para obtenção do leite de qualidade, porém as PL's estudadas não condiziam com essa realidade proposta pelas normas sanitárias da legislação em vigor.…”
Section: Caracterização Dos Produtores E Das Pl's a B C D E E Avalunclassified